Analisis Pola Produktivitas Harian Karyawan BTPN Syariah melalui Metode Clustering K-Medoids untuk Peningkatan Kinerja Pegawai Cabang Solokan Jeruk - Angelina, Dina (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
\The fierce competition in the financial sector pushes institutions like BTPN Syariah to ensure their human resources remain capable and efficient. Assessments of work performance, often done manually and based on subjective judgment, fall short in reflecting employee productivity fully. For that reason, the current study seeks to examine daily productivity patterns among BTPN Syariah employees at the Solokan Jeruk Branch using the K-Medoids clustering approach. This technique groups employees according to clear productivity measures, including attendance rates, target achievements, time management, and teamwork roles. The findings reveal two distinct groups with varying work patterns, allowing management to grasp each group’s traits objectively and craft better-suited development plans. The study also supports data-based decision-making in workforce management while aiding in enhancing efficiency and service quality for customers.